DEVELOPMENT OFPRESSURE MODIFICATION INDEX-/IN RATE BASED MODEL FOR C02 REMOVAL AT ELEVATED PRESSURE - ISA, FAEZAH (2016)
Standard rate-based non-equilibrium model has been widely used to model CO2 removal via absorption in post-combustion processes. However, this common process ofCO2 removal is normally conducted at atmospheric pressure while acid gas treatment in natural gas processing is typically conducted at high pressure. Pressure significantly influenced the thermodynamics aswell asthe hydrodynamics and mass transfer aspects. Hence, standard rate based non-equilibrium model failed at elevated pressure due to this reason. In this research, the standard rate based non-equilibrium model has been modified to incorporate pressure modification index-/based on hydrodynamics and mass transfer. Standard ratebased non-equilibrium model has beenreplicated using the work of Pandya for pressure ranging from 20 bar to 60 bar which includes reaction kinetics, mass transfer rate, and heat transfer and enhancement factor. Various hydrodynamic parameters have been analyzed and the result shows only combination of mass transfer coefficient and effective interfacial area coefficient from Billet & Schultes give the most reliable predicted height whichis around 7.22mcompared to the actual column height which 1.505m.